2013
DOI: 10.1175/jamc-d-13-038.1
|View full text |Cite
|
Sign up to set email alerts
|

Urban Emissions of CO2 from Davos, Switzerland: The First Real-Time Monitoring System Using an Atmospheric Inversion Technique

Abstract: Anthropogenic emissions from urban areas represent 70% of the fossil fuel carbon emitted globally according to carbon emission inventories. The authors present here the first operational system able to monitor in near-real time daily emission estimates, using a mesoscale atmospheric inversion framework over the city of Davos, Switzerland, before, during, and after the World Economic Forum 2012 Meeting (WEF-2012). Two instruments that continuously measured atmospheric mixing ratios of greenhouse gases (GHGs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 29 publications
4
94
0
Order By: Relevance
“…Additionally, Angevine et al (2014) have shown that using an ensemble mean of model simulations with different meteorology does not necessarily lead to a better representation of plume transport and dispersion in a Lagrangian model for area sources. We therefore speculate that assimilating observed wind fields in WRF-Chem, as was done by Lauvaux et al (2013), could be more beneficial to improve the modelled wind fields and as such improve the plume transport. Furthermore, the model performance under stratified and low wind-speed conditions needs to be addressed, since removing these data can lead to biased emission estimates.…”
Section: Model Skillmentioning
confidence: 99%
“…Additionally, Angevine et al (2014) have shown that using an ensemble mean of model simulations with different meteorology does not necessarily lead to a better representation of plume transport and dispersion in a Lagrangian model for area sources. We therefore speculate that assimilating observed wind fields in WRF-Chem, as was done by Lauvaux et al (2013), could be more beneficial to improve the modelled wind fields and as such improve the plume transport. Furthermore, the model performance under stratified and low wind-speed conditions needs to be addressed, since removing these data can lead to biased emission estimates.…”
Section: Model Skillmentioning
confidence: 99%
“…Consequently, there is an increasing deployment of urban CO 2 monitoring networks with the objective of quantifying city emissions through the atmospheric inversion approach (Boon et al, 2016;Duren and Miller, 2012;Lauvaux et al, 2013Lauvaux et al, , 2016Kort et al, 2013;McKain et al, 2012;Strong et al, 2011;Turnbull et al, 2015). Bréon et al (2015), upon which this study builds, recently reported first estimates of fossil fuel CO 2 emissions of the Paris urban area during a 2-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Initial results are based on dedicated urban ground-based atmospheric CO 2 measurement networks (Breon et al, 2015;Lauvaux et al, 2013;Turnbull et al, 2015). There has been no attempt at using SCIAMACHY or GOSAT data at this scale due to the low resolution and precision of the SCIA-MACHY data or to the scarcity of the sampling by GOSAT.…”
Section: Introductionmentioning
confidence: 99%